Psikoedukasi dan Pelatihan Deteksi Dini Perkembangan Kepada Ibu untuk Optimalisasi Tumbuh Kembang Siswa TK Islam Nuria: Psychoeducation and Early Developmental Screening Training for Mothers to Optimize the Development of Students at TK Islam Nuria - Juliarni Siregar; Rachmayati Eka Safitri; Eko Handrian; Ega Octaviani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The challenges TK Islam Nuria faces in collaborating with parents to optimize child development highlight the importance of this community service program. The program aimed to enhance parental knowledge of child growth and development, including appropriate stimulation, and to improve skills in early detection of developmental issues. The program comprised psychoeducation to enhance knowledge of child development and stimulation, and training to develop skills in applying developmental screening instruments. The implementation of the program was analyzed using a quantitative research method, namely a quasi-experimental one-group pretest–posttest design. Statistical analysis using the Wilcoxon matched-pairs test revealed a significant increase in knowledge (p = 0.005 < 0.05) between before and after the psychoeducation intervention. The average pre-test score of 4.25 increased to 7.55 in the post-test, reflecting a gain of 3.3 points. Furthermore, all participants demonstrated the ability to apply screening instruments to identify developmental progress and potential barriers. These findings confirm that psychoeducation and training effectively strengthen parental knowledge and skills in early detection. The program's sustainability is supported by distributing guidebooks on developmental detection and stimulation to schools and parents. Follow-up for identified developmental obstacles is facilitated through individual psychological consultation services provided by professional psychologists, ensuring program integration. Future improvements are recommended, particularly by adding structured parenting programs.